2021
DOI: 10.3389/fphar.2021.682135
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation of Dosing, Bacterial Kill, and Resistance Suppression for Zoliflodacin Against Neisseria gonorrhoeae in a Dynamic Hollow Fiber Infection Model

Abstract: Antimicrobial resistance in Neisseria gonorrhoeae is threatening the treatment and control of gonorrhea globally, and new treatment options are imperative. Utilizing our dynamic in vitro hollow fiber infection model (HFIM), we examined the pharmacodynamics of the first-in-class spiropyrimidinetrione (DNA gyrase B inhibitors), zoliflodacin, against the N. gonorrhoeae reference strains World Health Organization F (susceptible to all relevant antimicrobials) and WHO X (extensively drug resistant, including resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…The WHO Global Action Plan to Control the Spread and Impact of Antimicrobial Resistance in N. gonorrhoeae ( WHO, 2012 ) and WHO Global Action Plan on Antimicrobial Resistance ( WHO, 2015 ) stress that new antimicrobials for treatment of urogenital and extragenital gonorrhea are imperative. Currently, solely two new antimicrobials, zoliflodacin ( Jacobsson et al, 2014 ; Alm et al, 2015 ; Basarab et al, 2015 ; Foerster et al, 2015 ; Unemo et al, 2015 ; Taylor et al, 2018 ; Foerster et al, 2019 ; O’Donnell et al, 2019 ; Unemo et al, 2019 ; Bradford et al, 2020 ; Jacobsson et al, 2021 ) and gepotidacin ( Jacobsson et al, 2018 ; Scangarella-Oman et al, 2018 ; Taylor et al, 2018 ), are in later stages of clinical development for treatment of uncomplicated gonorrhea.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The WHO Global Action Plan to Control the Spread and Impact of Antimicrobial Resistance in N. gonorrhoeae ( WHO, 2012 ) and WHO Global Action Plan on Antimicrobial Resistance ( WHO, 2015 ) stress that new antimicrobials for treatment of urogenital and extragenital gonorrhea are imperative. Currently, solely two new antimicrobials, zoliflodacin ( Jacobsson et al, 2014 ; Alm et al, 2015 ; Basarab et al, 2015 ; Foerster et al, 2015 ; Unemo et al, 2015 ; Taylor et al, 2018 ; Foerster et al, 2019 ; O’Donnell et al, 2019 ; Unemo et al, 2019 ; Bradford et al, 2020 ; Jacobsson et al, 2021 ) and gepotidacin ( Jacobsson et al, 2018 ; Scangarella-Oman et al, 2018 ; Taylor et al, 2018 ), are in later stages of clinical development for treatment of uncomplicated gonorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…No clinical N. gonorrhoeae isolates with zoliflodacin resistance have been reported when international gonococcal populations from the last decade have been examined ( Jacobsson et al, 2014 ; Unemo et al, 2015 ; Unemo et al, 2019 ; Bradford et al, 2020 ; Le et al, 2021 ). However, in static in vitro laboratory experiments zoliflodacin-resistant mutants have been selected; all containing substitutions of amino acids D429 or K450 of GyrB ( Alm et al, 2015 ; Foerster et al, 2015 ; Foerster et al, 2019 ; Jacobsson et al, 2021 ). No clinical isolate with amino acid substitution in GyrB K450 and only one single clinical isolate with a GyrB D429V substitution has been found ( Jacobsson et al, 2014 ; Alm et al, 2015 ; Unemo et al, 2015 ; Unemo et al, 2019 ; Bradford et al, 2020 ; Le et al, 2021 ; Adamson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three years later, an in vitro study of 1209 consecutive clinical N. gonorrhoeae isolates did not reveal any cross-resistance to ciprofloxacin, azithromycin, cefixime, and ceftriaxone [ 135 ]. Patients should take at least 2 g of a single oral dose treatment of zoliflodacin to obtain effective N. gonorrhoeae suppression [ 136 ]. Additionally, studies revealed that the conventional therapeutic dose of 2 g does not induce cardiac arrhythmias and is well tolerated [ 137 ].…”
Section: Novel Drugs and Nano Moleculesmentioning
confidence: 99%